2002
DOI: 10.1161/01.cir.0000036747.68104.ac
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Valsartan on Circulating Brain Natriuretic Peptide and Norepinephrine in Symptomatic Chronic Heart Failure

Abstract: Background-Brain natriuretic peptide (BNP) and norepinephrine (NE) are strongly related to severity of and are independent predictors of outcome in heart failure. The long-term effects of angiotensin receptor blockers on BNP and NE in heart failure patients are not known. Methods and Results-Both BNP and NE were measured in 4284 patients randomized to valsartan or placebo in the Valsartan Heart Failure Trial (Val-HeFT) at baseline and 4, 12, and 24 months after randomization. The effects of valsartan were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(50 citation statements)
references
References 25 publications
4
43
0
3
Order By: Relevance
“…ARB can modulate neurohormon on RAA system, that result in decreasing NTproBNP level on valsartan vs enalapril show decrease 15% vs 13% after 12 months therapy (Lee et al 2011, Masson et al 2008, Kasama et al 2006, Latini et al 2002. In this study, we also have similar result as previous study, that NT-proBNP decrease significantly (p=0,003) after 2 months therapy.…”
Section: Discussionsupporting
confidence: 86%
“…ARB can modulate neurohormon on RAA system, that result in decreasing NTproBNP level on valsartan vs enalapril show decrease 15% vs 13% after 12 months therapy (Lee et al 2011, Masson et al 2008, Kasama et al 2006, Latini et al 2002. In this study, we also have similar result as previous study, that NT-proBNP decrease significantly (p=0,003) after 2 months therapy.…”
Section: Discussionsupporting
confidence: 86%
“…[23][24][25][26] In ambulatory patients, there is now a considerable body of evidence showing that ACE inhibitors, angiotensin II receptor 1 antagonists, and spironolactone decrease BNP levels. 21,[23][24][25][26] The decrease of BNP in response to ␤-blockers is observed after 6 to 12 months of therapy. 27 A pilot study reported that HF therapy guided to decrease NT-proBNP levels is associated with improved prognosis compared with therapy according to clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Measurement of BNP 4 months apart in the Valsartan Heart Failure Trial (Val-HeFT) provided additional prognostic information. Patients with an increase in BNP levels Ͼ30% had an almost double mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect NT-proBNP concentrations, including extracellular volume (12), cardiac rhythm (13), myocardial ischemia (14,15), the dialysis prescription (16), and cardiac pharmacotherapy (17)(18)(19). These influences were assessed at every visit using a structured clinical interview, physical examination, and medical records review to ascertain interim hospitalization and changes to medication and/or the dialysis prescription.…”
Section: Patient Assessmentmentioning
confidence: 99%